Possible Novel Treatment Modality for Non Ossifying Fibroma Neck of Femur - Mohammed Alam Parwaz; Tarun Chaudhary; Suraj Bansal (Indian Journal of Plastic Surgery)
Nonossifying fibromas (NOFs) are benign bone tumors occurring in the second decade of life. Most of the NOFs are diagnosed incidentally on the basis of its presentation on plain radiographs where they typically appear as small, cortical osteolytic lesions with sclerotic margin. They are mostly asymptomatic but can result in pathologic fractures if the lesion involves more than 50% of bone diameter. They are mostly treated with curettage and bone grafting. But in challenging situations where the classical surgery has failed or there is impending fracture of the neck of femur, bone structural support is needed. We are discussing two cases diagnosed as NOFs of intracapsular femoral neck. Both cases underwent curettage of tumor followed by free vascularized fibular graft. Results in both the cases were very gratifying, with complete resolution of symptoms during 1 year of follow-up.